Desain Media Tour The Zoo Melalui TGT pada Materi Ekosistem Meningkatkan Critical Thinking dan Problem Solving Siswa Kelas V SD - Tsaniatul Muyassaroh; Mohamad Fatih; Cindya Alfi (Science and Education Journal (SICEDU), 2026)
This study aims to develop Tour The Zoo (TTZ) learning media through the Teams Games Tournament (TGT) model on ecosystem material to improve critical thinking and problem solving skills of fifth grade elementary school students. This study uses the Research and Development (R&D) method with the Borg and Gall model which is simplified into seven stages, namely research and data collection, planning, initial product development, initial field trials, product revision, main field trials, and operational product revisions. The research subjects were 17 fifth grade students at SDN 3 Kepanjenlor, Blitar City with data collection techniques in the form of observation, interviews, questionnaires, and pretest-posttest tests. Data analysis was carried out through validity tests, reliability tests, prerequisite tests, paired sample t-tests, and MANOVA. The results of the study showed that the percentage of media expert validation was 91% and material expert validation was 100%. The results of teacher responses also showed a percentage of 100% with a very feasible category. In addition, the results of the hypothesis test showed an increase in students' critical thinking and problem solving abilities after the use of TTZ media. The results of the MANOVA test show that TTZ media through the TGT model has a significant influence on increasing critical thinking and problem solving abilities simultaneously.